Treatment of bone metastases in breast cancer patients - Pawlak, Wojciech Z.; Wawrocka-Pawlak, Marlena (Contemporary Oncology/Współczesna Onkologia, 2006)
Bone metastases are a major problem in the clinical management of patients with breast cancer. With prolongation of survival, the challenge is to improve the quality of the patient’s remaining life. The treatment of metastatic bone disease requires a multidisciplinary approach that addresses systemic and focal disease. The complex nature of metastatic disease requires the combined efforts of a team of clinical, radiation, and orthopaedic oncologists. Prevention and treatment of skeletal complications requires early detection and aggressive management. Focal complications are best treated with both surgery and radiotherapy. Systemic disease and complications are best addressed with hormonal therapy, chemotherapy, and bisphosphonate therapy. External-beam radiotherapy has become a mainstay in the palliative treatment of metastatic bone disease. The indications for radiotherapy are the relief of pain and the control of localized disease. Bisphosphonates, as inhibitors of osteoclast activity, are very effective in the prevention of skeletal complications and hypercalcaemia.